Automated planning theory and practice - Ghallab, Malik (Elsevier/Morgan Kaufmann, 2004)
Automated planning technology plays a significant role in a variety of demanding applications, ranging from controlling space vehicles and robots to playing the game of bridge. This book covers both the theory and practice of automated planning. It is useful for researchers, professionals, and graduate students.
Includes bibliographical references (pages 573-607) and index. - Print version record
Keywords: Production planning -- Data processing; Production; Planification; Informatique; BUSINESS & ECONOMICS; Production & Operations Management; TECHNOLOGY & ENGINEERING; Industrial Engineering; TECHNOLOGY & ENGINEERING; Industrial Technology; Production planning; Data processing; Planejamento da produção; Processamento de dados; dissertations; Academic theses; Thèses et écrits académiques